Developing an Integrated Innovation Ecosystem to Strengthen Islamic Economy in Indonesia - Sugeng Santoso; Ginanjar Dewandaru; Nugroho, Lucky; Hidayat, Sutan Emir; Salmi Mohd Isa; Hidayat, R Nur; Muhammad Ramadhani Marfatah (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This research attempts to develop an integrated innovation ecosystem of Islamic economy, which focuses on vocational education and training. We integrate the vocational education and training into the supply-demand-linkage of innovation ecosystem, within the key sectors of Islamic economy. We also refer to the underlying regulation which is the President Decree No. 68 Year 2022 about Revitalization of Vocational Education and Training. The sample of observations is the relevant stakeholders in the Province of East Java, that include industry players, government, and vocational education institutions. The key sectors of Islamic economy include the industry of halal processed F&B and pharmaceuticals, halal agriculture and fishery, as well as Muslim-friendly tourism and Islamic creative economy, which are selected based on their percentage of contribution to the overall regional GDP. We use both quantitative and qualitative approach, by deriving data and information from Focus Group Discussions (FGD) and questionnaires. Whereby, qualitative approach is used by conducting in-depth discussions and interviews with relevant stakeholders. The findings of this study show the strength and weakness for each of the supply-demand-linkage model, suggesting the policy direction in order to improve the productivity factors of human resources.